2017
DOI: 10.1021/acs.inorgchem.6b01956
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Primary and Secondary Coordination Spheres within a Series of CoII—OH Complexes

Abstract: The interplay between the primary and secondary coordination spheres is crucial to determining the properties of transition metal complexes. To examine these effects, a series of trigonal bipyramidal Co–OH complexes have been prepared with tripodal ligands that control both coordination spheres. The ligands contain combination of either urea or sulfonamide groups that control the primary coordination sphere through anionic donors in the trigonal plane and the secondary coordination sphere through intramolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…18 Central to the syntheses is the diurea compound, 1,1′-((2aminoethyl)azanediyl)bis(ethane-2,1-diyl))bis(3-( tert- butyl)urea which is combined in the final step with diphenylphosphinic chloride in THF and excess Et 3 N. Precipitation of the ammonium chloride salt was observed immediately, and H 5 pout was isolated as a white solid in 85% yield after purification.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Central to the syntheses is the diurea compound, 1,1′-((2aminoethyl)azanediyl)bis(ethane-2,1-diyl))bis(3-( tert- butyl)urea which is combined in the final step with diphenylphosphinic chloride in THF and excess Et 3 N. Precipitation of the ammonium chloride salt was observed immediately, and H 5 pout was isolated as a white solid in 85% yield after purification.…”
Section: Resultsmentioning
confidence: 99%
“…Similar structural results were found in Co–OH complexes and emphasized the structural effects of the H-bonds within the secondary coordination sphere. 18 Notice also potassium ion does not interact with the Mn–OH unit in the lattice of K[Mn III H 2 pout(OH)]; it only interact with the carbonyl groups of the ureas which are pointed away from the hydroxido ligand (Figure 3D). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ), which we and others have shown can produce metal complexes with diverse structures and functions. 29 41 For this study, we have incorporated sterically encumbering triisopropylbenzene groups to support the formation of a coordinatively unsaturated monomeric Fe II complex. We demonstrated that the metal center remains accessible to endogenous ligands by producing bipyridine adducts whose oxidative properties we have also defined.…”
Section: Introductionmentioning
confidence: 99%